Pembelajaran Bahasa Indonesia di Taman Pendidikan Al-Qur`an (TPA) Menggunakan Pop Up (Learning Indonesian at Al-Qur`an Learning Center Using Pop Up) - Syihaabul Hudaa; Nuryani Nuryani; Elen Inderasari (Indonesian Language Education and Literature, 2021)
The lack of teacher competence in making creative and informative learning media makes the learning atmosphere less pleasant. This study aims to describe the use of pop-ups in Indonesian language learning at the Al-Qur`an Learning Center (TPA). This research belongs to the type of descriptive qualitative using a classroom action research (PTK) approach. This research was conducted in August-November 2019. The stages of the research include: 1) introducing pop-ups and their manufacturing techniques, 2) the teacher applies them in Indonesian language learning activities at the TPA, and 3) describes the effectiveness of pop-up media in learning activities. The results showed that pop-up media was very effective to be applied in learning activities at the TPA. The increase in students' reading and writing skills occurs because pop-ups make students enthusiastic in learning activities.Kurangnya kompetensi guru dalam membuat media pembelajaran yang kreatif dan informatif membuat suasana pembelajaran menjadi kurang menyenangkan. Penelitian ini bertujuan untuk mendeskripsikan penggunaan pop up pada pembelajaran bahasa Indonesia di Taman Pendidikan Al-Qur`an (TPA). Penelitian ini termasuk ke dalam jenis kualitatif deskriptif dengan menggunakan pendekatan penelitian tindakan kelas (PTK). Penelitian ini dilakukan Agustus—November 2019. Tahapan penelitian, meliputi: 1) mengenalkan pop up dan teknik pembuatannya, 2) guru menerapkan dalam kegiatan pembelajaran bahasa Indonesia di TPA, dan 3) mendeskripsikan keefektifan media pop up dalam kegiatan pembelajaran. Hasil penelitian menunjukkan bahwa media pop up sangat efektif diterapkan dalam kegiatan pembelajaran di TPA. Peningkatan kemampuan siswa dalam membaca dan menulis terjadi karena pop up membuat siswa antusias dalam kegiatan belajar.